Penyuluhan Cuci Tangan pada Anak untuk Meningkatkan Kesadaran Hidup Sehat di SDN 2 Dukuhdamu Slawi - Ratna Widhiastuti; Ramadhan Putra Satria; Finka Akhiria Wati; Naurah Nazifah; Mauliana Ajeng Pramesti; Yores Putri Sakinah; Anggit Pratiwi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Infectious diseases often spread through hand contact, and good handwashing practices are a crucial step in preventing infection transmission. This community engagement activity aims to provide handwashing education to students at Elementary School (SDN) 2 Dukuhdamu in Slawi. The activity was conducted using educational methods and monitoring student participation in handwashing practices. The results showed a significant improvement in knowledge and handwashing behavior among students after the education. These findings highlight the importance of health education in schools in promoting healthy lifestyles.